Turkish Adaptation of the Health Improvement Profile for the Evaluation of Physical Well-Being of Individuals With Severe Mental Illness - Merve Murat; Fatma Yasemin Kutlu (AVES, 2024)
AIM: This study aimed to adopt the use of the Health Improvement Profile in the Turkish context and to report the findings obtained during its pilot implementation. METHODS: This descriptive cross-sectional study consisted of 280 individuals, and data were collected using the Patient and Disease Characteristics Form and the Health Improvement Profile between May and December 2019 ın community mental health centers. The total content validity index of the Health Improvement Profile (Female-Male) was 0.97. RESULTS: Among the participants, 57.1% had a physical health problem, 58.1% had a diagnosis of a physical condition, and 41.9% had physical symptoms only. Intergroup comparisons showed that individuals diagnosed with schizophrenia and other psychotic disorders slept for less than 3 hours, individuals diagnosed with bipolar disorder consumed more alcohol, and individuals diagnosed with major depressive disorders slept for more than 8 hours, smoked more, consumed more caffeine, and practiced safe sex less consistently than individuals diagnosed with other psychiatric disorders (p < .05). CONCLUSION: The Health Improvement Profile is an assessment tool that psychiatric mental health nurses can use to evaluate the physical health of individuals diagnosed with serious mental illness. The use of Health Improvement Profile in routine practice may allow determining the redflagged parameters and provide an opportunity improving these parameters with evidence-based interventions.